2021
DOI: 10.1038/s41598-021-91363-4
|View full text |Cite
|
Sign up to set email alerts
|

Housing quality and behavior affect brain health and anxiety in healthy Japanese adults

Abstract: Countless studies in animals have shown how housing environments and behaviors can significantly affect anxiety and brain health, giving valuable insight as to whether this is applicable in the human context. The relationship between housing, behavior, brain health, and mental wellbeing in humans remains poorly understood. We therefore explored the interaction of housing quality, weekend/holiday sedentary behavior, brain structure, and anxiety in healthy Japanese adults. Whole-brain structural magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Studies published in recent literature have started investigating, in a systematic way, the overall quality of built environment [ 29 , 30 ] and living spaces, revealing that the absence of accessible outdoor space from the house (e.g., garden, terrace) contributed to concerning levels of psychological and behavioral symptomatology [ 31 ], confirming that housing environments could be associated with the mental health and wellbeing of residents [ 32 , 33 , 34 , 35 , 36 ]. While mental illnesses can be investigated through structured and validated scales, housing quality is mainly assessed in terms of occupants’ perception, due to the complexity of surveying a high number of different apartments and the low psychometric reliability of existing tools [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies published in recent literature have started investigating, in a systematic way, the overall quality of built environment [ 29 , 30 ] and living spaces, revealing that the absence of accessible outdoor space from the house (e.g., garden, terrace) contributed to concerning levels of psychological and behavioral symptomatology [ 31 ], confirming that housing environments could be associated with the mental health and wellbeing of residents [ 32 , 33 , 34 , 35 , 36 ]. While mental illnesses can be investigated through structured and validated scales, housing quality is mainly assessed in terms of occupants’ perception, due to the complexity of surveying a high number of different apartments and the low psychometric reliability of existing tools [ 37 , 38 , 39 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous studies, whole-brain level GM-BHQ showed a positive correlation with dietary balance 23 ,curiosity 24 , and behavioral activation 27 as well as negatively correlated with fatigue 25 and unhealthy lifestyles 26 . Similarly, it was shown that whole-brain FA-BHQ was positively correlated with cognitive function, fish diet intake 22 , housing quality, and anxiety 76 .…”
Section: Mri Data Acquisitionmentioning
confidence: 87%
“…Elevated glucocorticoid levels due to stress could have inhibitory effects on steroidogenesis, spermatogenesis, and sperm maturation. A study indicated that psychological stress among men at the time of oocyte retrieval had negative impacts on sperm quality 39 . Moreover, a crosssectional study showed a negative association between self-reported stress and sperm parameters 40 .…”
Section: Discussionmentioning
confidence: 99%